Growth and Physiological Responses of Azadlrachta Excelsa (Jack) Jacobs to Fertilizer and Mycorrhizal Applications - Ong, Kian Huat (1998)
Azadirachta excelsa (Jack) Jacobs is a fast growing multi-purpose tree species and is one of the species that is being promoted for planting in Malaysia. However, the silvicultural requirements of the species have not been well defined. The objective of this study was to evaluate the effects of fertilizers, mycorrhizal inoculation and mixed planting with A cacia mangium Willd seedlings on the growth and physiological changes of A. excelsa seedlings on Rengam series soil. The study consisted of two components. The pot trial examined the physiological changes and growth performance of A. excelsa seedlings in response to various fertilizer and mycorrhizal treatments using soil collected from the field. The field trial examined the seedling performance under field conditions when applied with fertilizer and mycorrhizal treatments, as well as mixed planted with A. mangium. Results from the four month pot trial showed that fertilized seedlings grew better than the control plants. Among the fertilizer treatments, Best-Tab slow release fertilizer (20-10-5 NPK with expanded minor and secondary element in 21 g tablet) promoted the best growth with maximum photosynthesis, followed by 40 g of NPK fertilizer (15-15-15 fertilizer (15-15-15 NPK) and finally 20 g of NPK fertilizer (15-15-15 NPK). In contrast, mycorrhizal application failed to promote seedling growth in a similar way. Similarly, combination of treatments failed to improve seedling growth as compared to either slow release fertilizer or NPK fertilizer alone.